To Combat White Collar Crimes In Public And Private Sector And Need For Strong Legislation And Ethics: Dr Aftab Ahmad Malik, Engr. Mujtaba Asad ,Waqar Azeem - Malik, Engr. Mujtaba Asad; Malik, Waqar Azeem (International Journal for Electronic Crime Investigation, 2020)
The paper deals with and investigates the requirement of resilient and strong legislation to combatwhite collar crimes, which are exponentially increasing with time both in public and private sectororganizations. The influence of immoral and illegal practices in government, particularly the bribesof the highest order has paralyzed the normal functioning of the financial and legislative organizations.Bank frauds and cybercrimes are also increasing tremendously by employing digital devicesand the internet. The purpose of this research is also to investigate the essence of the application ofstrong laws as well principles of morality and ethics. It is advocated by the authors of this paper thatnorms of morality and ethics on one hand impact a healthy effect on reducing such crimes but alsoenhances the productivity and profitability of the organizations in financial terms. Several modernorganizations are incorporating and implementing the codes of ethics in professional practices.More strict must be the legislation and Code of Ethics, Ethics is the deterrence force to discouragethe wrongdoings and adopting right approach so that honesty prevails and curses, crimes, offensesand sins can be minimized. There a serious need of introducing the social welfare system adopted inEurope, Canada and the USA. The bank employees are involved in Bank frauds and commit offensesof embezzlements and illegal transitions using the computer and other digital devices. The role ofbusiness ethics in the banking sector is of immense importance. The malpractices by some politiciansmust also be noticed with stern and iron hands.